Об академическом комментарии к поэзии модернизма (Случай Ахматовой) [An Academic Commentary on Modernist Poetry: The Case of Akhmatova] - Timenchik, Roman (Slavica Revalensia, 2023)
This article is the extended version of the keynote lecture Roman Timenchik delivered on May 12, 2023 at Tallinn University at the opening ceremony of a newly established Graduate Student Conference in Russian Language and Literatures (Helsinki—Tallinn—Tartu). Roman Timenchik singles out five principles of annotating a text and the eleven sections required for the ideal annotated edition of Anna Akhmatova’s poetry.